2000
DOI: 10.1002/(sici)1097-0215(20000101)85:1<1::aid-ijc1>3.3.co;2-f
|View full text |Cite
|
Sign up to set email alerts
|

Induction of apoptosis by abrogation of HSP70 expression in human oral cancer cells

Abstract: Oral squamous cell carcinoma (SCC) is the most common cancer among males and ranks among 5 common cancers in females in India (Gupta, 1993). The high incidence of oral cancer in the Indian subcontinent is causally associated with the widespread habit of tobacco and betel quid chewing. The etiology of oral SCC in the betel-and tobacco-abused Indian population is considerably different as compared with Western populations. Betel quid chewing induces physical abrasions, which might create a mitogenic environment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 0 publications
0
21
0
Order By: Relevance
“…Furthermore, Carratelli et al [36] reported that lipids supplementation could up-regulate the protein levels of 70-kDa heat shock protein (hsp70) in mouse splenic lymphocytes. Studies indicate that up-regulating hsp70 could protect human liver cells from apoptosis [37]. Based on these results, we speculate that lipids may modulate antioxidant enzyme activities, GSH content, Nrf2 and Keap1 signalling molecules and apoptosis in fish immune organs, and the possibility is worthy of investigation.…”
Section: Introductionmentioning
confidence: 77%
“…Furthermore, Carratelli et al [36] reported that lipids supplementation could up-regulate the protein levels of 70-kDa heat shock protein (hsp70) in mouse splenic lymphocytes. Studies indicate that up-regulating hsp70 could protect human liver cells from apoptosis [37]. Based on these results, we speculate that lipids may modulate antioxidant enzyme activities, GSH content, Nrf2 and Keap1 signalling molecules and apoptosis in fish immune organs, and the possibility is worthy of investigation.…”
Section: Introductionmentioning
confidence: 77%
“…Interestingly, expression of Hsp70 was reported to protect cells against death stimuli (Jaattela and Wissing, 1993;Mosser et al, 1997;Parcellier et al, 2003). Increased Hsp70 expression in tumours also correlates with evasion from apoptosis (Ciocca et al, 1993;Wei et al, 1995;Jaattela, 1999;Kaur et al, 2000). Hsp70 was further shown to inhibit the activation of procaspase-3, but not the activity of processed caspase-3 (Mosser et al, 1997;Li et al, 2000;Mosser et al, 2000;Saleh et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…The balance between immunogenic (Blachere et al, 1997;Udono and Srivastava, 1993) and anti-apoptotic (Beere et al, 2000;Jaattela et al, 1998;Saleh et al, 2000) e ects of this stress protein may account for the contradictory reports assessing a role for HSP70 expression in malignant cell tumorigenicity and immunogenicity (Jaattela, 1995;Kaur and Ralhan, 1995;Ralhan and Kaur, 1995;Seo et al, 1996;Volloch and Sherman, 1999;Wells and Malkovsky, 2000). Limited expression of the protein, below an antiapoptotic level, could contribute to tumor cell immunogenicity when being released from dying cells (Kaur and Ralhan, 2000;Nylandsted et al, 2000).…”
Section: Discussionmentioning
confidence: 99%